Health Hazards and Knowledge about Junk Foods-A Review - Krishna Pawar, Vaishali (International Journal of Nursing Research, 2023)
In consumer societies, modern diets based on unhealthy fast foods, convenience foods, energy dense snacks, and soft drinks, the abundance and omnipresence of food, and sedentary lifestyles and electronic recreation that minimizes physical activity have led to serious weight control problems. A particularly severe trend impacting future health levels are the high, and in most countries still rising, levels of overweight and obesity in infants and children. Junk food tastes good, but the effects on the health is detrimental. Junk foods have become a prominent feature of the diet of youngsters, especially in the developing country. The health problems that stem from overweight and obesity can shorten the life span. Future medical practitioners should know that these kinds of eating habits will create nutritional deficiencies along with weight gain which ultimately ends in metabolic syndrome. In this review, we will discuss health hazards of junk food and knowledge and opinions of the adolescents.